2008
DOI: 10.1051/mmnp:2008055
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Feedback in Engineering and Biology

Abstract: Abstract. No other concepts have shaken so deeply the bases of engineering like those of positive and negative feedback. They have played a most prominent role in engineering since the beginning of the previous century. The birth certificate of positive feedback can be traced back to a pair of patents by Edwin H. Armstrong in 1914 and 1922, whereas that of negative feedback is already lost in time. We present in this paper a short review on the feedback's origins in the fields of engineering and biology. Besid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The binding of active repressors to the first two operators occurs cooperatively and this increases the sigmoidicity of the regulatory function accounting for repression [4,14]. Furthermore, it has been shown that a high level on sigmoidicity is necessary for the the bacteria to maintain a constant intracellular tryptophan concentration, regardless of variations in the amino acid concentration in the extracellular medium [16].…”
Section: Discussionmentioning
confidence: 99%
“…The binding of active repressors to the first two operators occurs cooperatively and this increases the sigmoidicity of the regulatory function accounting for repression [4,14]. Furthermore, it has been shown that a high level on sigmoidicity is necessary for the the bacteria to maintain a constant intracellular tryptophan concentration, regardless of variations in the amino acid concentration in the extracellular medium [16].…”
Section: Discussionmentioning
confidence: 99%
“…Positive feedback can amplify the properties of thermal input/concentration output systems processed by chemical reactions. Such properties have been studied mathematically through systems biology [47][48][49][50][51]. It is thus interesting experimentally to study such properties, which can promote understanding of biological phenomena and development of novel material functions.…”
Section: Positive Feedback By Self-catalytic Chemical Reactionmentioning
confidence: 99%
“…While feedback is a function of interest in both SB and EB and it has been known for at least half a century in medicine and two millennia in physics [22]–[25], feedback has only marginally been explored in infections. In October of 2012, more than 200,000 bibliographic hits could be retrieved under ‘feedback’ and ∼1700 hits were yielded when ‘feedback’ and ‘definition’ were searched for, but less than 50 hits were found when ‘infection’ was added.…”
Section: Introductionmentioning
confidence: 99%